Lung Cancer and Radiological Imaging - Panunzio, Annalori; Sartori, Paolo (Current Radiopharmaceuticals, 2020)
Background: Lung cancer is the neoplasm with the highest prevalence and mortality rates in the world. Most patients with lung cancer that are symptomatic have hemoptysis, coughing, shortness of breath, chest pain and persistent infections. Less than 10% of patients are asymptomatic when the tumor is detected as an incidental finding. Objective: The present expert review aims to describe the use of radiological imaging modalities for the diagnosis of lung cancer. Methods: Some papers were selected from the international literature, by using mainly Pubmed as a source. Results: Chest x-ray (CXR) is the first investigation performed during the workup of suspected lung cancer. In the absence of a rib erosion, CXR cannot distinguish between benign and malignant masses, therefore computed tomography (CT) with contrast enhancement should be performed in order to obtain a correct staging. Magnetic resonance imaging of the chest is considered a secondary approach as the respiratory movement affects the overall results. Conclusion: Radiological imaging is essential for the management of patients affected by lung cancer.
Keywords: MRI